1990
DOI: 10.1093/ptj/70.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Productivity: A Regional Study of Physical Therapy Faculty in Schools of Allied Health

Abstract: A study of the scholarly activities of physical therapy faculty members in selected schools of allied health was conducted through a mailed questionnaire survey. The analysis of the data provided by the respondents (N = 127; 97.6%) revealed the following: 1) the respondents' primary scholarly activity was authorship of referred journal articles; 2) a majority of the respondents presented a paper at a professional meeting during the past three years; 3) only a small percentage of the respondents had directed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…We found that eight subjects (17.8%) had no indexed publications, consistent with findings in 2009 from self-reported data of entry-level DPT faculty [12]. In contrast, a study of SE program faculty performed in 1987 identified 30% of 127 respondent self-reporting physical therapy faculty as not having authored a scholarly work [11] indicating a possible increase in research productivity over the past 30 years. The faculty that represented the median received 53 total citations for scholarly work in indexed publications; a total of 11 subjects (24.4%) had received zero citations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that eight subjects (17.8%) had no indexed publications, consistent with findings in 2009 from self-reported data of entry-level DPT faculty [12]. In contrast, a study of SE program faculty performed in 1987 identified 30% of 127 respondent self-reporting physical therapy faculty as not having authored a scholarly work [11] indicating a possible increase in research productivity over the past 30 years. The faculty that represented the median received 53 total citations for scholarly work in indexed publications; a total of 11 subjects (24.4%) had received zero citations.…”
Section: Discussionsupporting
confidence: 74%
“…The decision to collect research productivity data from promoted and tenured DPT professors in specific regions of the country and calculating individual regional findings is supported by previous reporting in the literature of region-specific scholarly productivity [11], and by the notion that ‘the geographical location of the university, too, could affect the resources, barriers, and productivity (e.g., pilot research studies) a faculty member experiences’ [9]. Such factors may include collaborative potential, the types of regional industries local to the institution, physical distance to other research institutions, and economic factors such as institutional funding and available real property assets at the institution.…”
Section: Introductionmentioning
confidence: 97%
“…Qualitative methods were an appropriate choice for our study because they can capture the lived experiences of others, 19 are flexible and dynamic, and produce rich description and detail. 20 The socialization paradigm 2,3,6 has been used previously 5,21 to explore the transition to practice and therefore provided the framework for our study by including both students' and faculty members' perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…When defining the profile of researchers and scientific production, international studies 1,4 have used a combination of bibliographic databases and reports from accredited research lecturers of undergraduate and graduate programs in physical therapy. However, this combination of sources was considered incomplete by researchers who endorsed the latest U.S. study 1 on the subject, which resulted in several letters to the editor 3,5,6 challenging the methodology.…”
Section: Introductionmentioning
confidence: 99%